Peer tutors as learning and teaching partners: a cumulative approach to building peer tutoring capacity in higher education - Clarence, Sherran (Critical Studies in Teaching and Learning, 2023)
Peer tutors in higher education are frequently given vital teaching and learning work to do, but the training or professional development and support opportunities they are offered vary, and more often than not peer tutors are under-supported. In order to create and sustain teaching and learning environments that are better able to facilitate students’ engagement with knowledge and learning, the role of peer tutors needs to be recognised differently, as that of learning and teaching partners to both lecturers and students. Tutors then need to be offered opportunities for more in-depth professional academic development in order to fully realise this role. This paper explores a tutor development programme within a South African writing centre that aimed at offering tutors such ongoing and cumulative opportunities for learning and growth using a balanced approach, which included scholarly research and practice-based training. Using narrative data tutors provided in reflective written reports, the paper explores the kinds of development in tutors’ thinking and action that are possible when training and development is theoretically informed, coherent, and oriented towards improving practice.